The Canadian dollar and commodity prices: Has the relationship changed over time? - Philipp Maier; Brian DePratto (Bank of Canada, 2008)
The authors examine the impact of the recent run-up in energy and non-energy commodity prices on the Canadian dollar. Using the Bank of Canadas' exchange rate equation, they find that the differences between the actual value of the Canadian exchange rate and the simulated values observed in 2007 are not historically large. Still, given that there is some evidence that the sensitivity of the standard exchange rate equation to changes in energy and non-energy commodities may have changed over time, the authors explore different ways of modelling the impact of energy and non-energy commodity prices. Their results indicate that specifications that explicitly consider the importance of energy and non-energy commodities in Canadas' export or production basket may yield more stable coefficient estimates, particularly over recent periods. Future research should investigate the robustness of these findings, particularly if, at some point, price increases for energy and non-energy commodities were to moderate.
Keywords: F31; 330; Exchange rates; Inflationsrate; Energieressourcen; Güter; Wechselkurs; Kanada